Kinetics of moisture loss and fat absorption during frying for different varieties of plantain - Díaz, A.; Trystram, G; Vitrac, O; Dufour, D.L.; Raoult-Wack, A.L. (Wiley, 1999)
This study compares the behaviour of four varieties of green plantain at their initial stage of maturity during the frying process. A variety traditionally used for the manufacture of thin plantain chips (Dominico Hartón commun) and three other varieties found in Latin America (Bouroukou, Bluggoe and FHIA 21) were used. The varieties were characterised by measuring initial moisture content, total sugar content, reducing sugar content, starch content and apparent density. Moisture loss and fat uptake kinetics during frying were assessed at different temperatures (145, 165 and 185°C). With all four varieties, the time required to produce a final moisture content of 40 g kg?1 (wb) was about 90 s at 165°C and 185°C. Use of a lower temperature (145°C) extended the processing time to 150 s. On the other hand, temperature had very little effect on fat content, which proved to be essentially determined by the variety of plantain. Fat content for final water content levels of 40 g kg?1 (wb) ranged from 300 g kg?1 (wb) for Bouroukou to 450 g kg?1 (wb) for Bluggoe regardless of the processing temperature.